Atlas of Bryum Hedw. Species from India - Nair, Swathi S; Murugan, Kumaraswamy; Sarayu, Manoj Gopal (Asian Journal of Biological and Life Sciences)
India is recorded as one of the mega biodiversity countries on the earth. The unique geographical zone and the physical-climatic features of the various biogeographic area resulted in the remarkable floral diversity of India. Bryophytes are small imaged amphibians with three different lineages such as liverworts, hornworts and moss. The category moss represents the largest group with more number of species. The present study aims to compile Bryum species of India based on all the available literature and information from herbaria of various organizations. Bryum is one of the largest genus among the moss species with morpho-plasticity of characters. Leaves form the unique character of the species, but a high discrepancy in leaves is recorded among the various species of the genus therefore it is wise to select other features unless it is established on specimens of diverse ecology. Sporophytic characters are ideal, but in most species, they remained unexplored as compared to the gametophytic datay. Similarly, the sporophytic capsules are highly diverse in size and their configuration is often irregular with abnormal peristomial characters. Further, the spores are diverse in size and shape. More than 45 species were recorded by various bryologists from India. Many species are similar in look with confusing characters. Therefore, revision of Bryum is warranted to eliminate the overlapping and complex allied clusters among the reported species.
Keywords: Bryophytes; Bryum; Characters; Distribution; India; Species diversity